Determination of size-independent effective permittivity of an overlay material using microstrip ring resonator - Jilani, M.T. (John Wiley and Sons Inc., 2016)
This letter describes a size-independent effective permittivity of biological tissues, using microstrip ring resonator (MRR), to evaluate the moisture content more effectively. As permittivity is depends on material density, the optimum sample size where further size variations will not change the effective permittivity are identified. Using simulation and experimental results it is found that, a sample having thickness more than 9 of substrate height (tsub) and width greater than 18.3 of guided wavelength (Î»g) shows size-independent effective permittivity. Both simulation and experimental results are in good agreement (within 3). These findings allow more effective characterization of muscles according to their moisture content. Â© 2016 Wiley Periodicals, Inc.